Effect of Ramie on the Production Performance of Laying Hens, and the Quality, Nutrient Composition, Antioxidation of the Eggs - Wang, Xin; Peng, Si-Min; Liu, Yang; Liao, Shuang; Zhao, Hao-Han; Duan, Guang-Ying; Wu, Yong-Mei; Liu, Chun-Jie; Wang, Yan-Zhou; Liu, Tou-Ming; Li, Ying-Hui; Fan, Zhi-Yong; et al. (Frontiers in Physiology, 2022)
Ramie (Boehmeria nivea), which is rich in protein, fatty acid, vitamins and minerals, has become a potential alternative feed resource for poultry, and has attracted more and more attentions in nutrition research. The objective of this study is to evaluate the effect of dietary ramie at different concentrations on the production performance of the hens, and the quality, nutrient composition, and antioxidation of the eggs. A total of 432 34-week-old Lohmann commercial laying hens were divided into 4 groups, that were fed with corn-soybean meal-based control diet, control mixed with ramie at concentrations of 3%, 6%, or 9% separately for 8 wk. Results showed that dietary ramie did not affect production performance. And egg yolk color gradually deepened as the inclusion levels of ramie increased. In addition, ramie at tested concentration could effectively reduce the content of Malondialdehyde (MDA) (P = 0.002) and 3% ramie supplementation significantly increased T-AOC concentrations in egg yolk compared to the one in control group (P = 0.033). For egg nutrient composition, compared with the control group, the addition of 6% ramie significantly increased (P < 0.05) total omega-3 polyunsaturated fatty acids (n-3PUFA) and phenylalanine (Phe) in yolk, and decreased (P < 0.05) the content of total cholesterol (T-CHO). In conclusion, dietary inclusion of 6% ramie were most effective in improving the color, antioxidative capability, and reducing T-CHO contents of the egg yolks without any negative impacts on the production performance of the hens.